2024
DOI: 10.2174/1567201820666221214105836
|View full text |Cite
|
Sign up to set email alerts
|

An Ex vivo Investigation on Drug Permeability of Sheep Nasal Epithelial Tissue Membranes from the Respiratory and Olfactory Regions

Abstract: Background: Besides systemic drug delivery, the intranasal route of administration has shown potential for direct nose-to-brain drug delivery, which has gained popularity because it bypasses the blood-brain barrier. Objective: The region in the nose from which the epithelial tissue membrane is excised to conduct ex vivo permeation studies for nasal drug delivery studies may be of importance, but the permeability of the epithelium from the different nasal regions has not yet been investigated in the sheep mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
2
0
0
Order By: Relevance
“…The permeation results of this ex vivo study are in agreement with the pharmacokinetic results obtained in an in vivo study reported by Hengjumrut et al [46] where the bioavailability of asiaticoside was higher when administered as a single compound, than when it was administered as an extract to rats. Furthermore, the P app values for both the asiaticoside alone and the C. asiatica crude extract across the respiratory tissue were similar to the P app values previously reported for atenolol across respiratory (P app = 0.67 ± 0.11 × 10 −6 cm/s) and olfactory (P app = 2.78 ± 0.36 × 10 −6 cm/s) nasal epithelial tissues, a drug with poor to medium permeability [47].…”
Section: Ex Vivo Permeation Studies With Centella Asiatica Crude Extr...supporting
confidence: 85%
See 1 more Smart Citation
“…The permeation results of this ex vivo study are in agreement with the pharmacokinetic results obtained in an in vivo study reported by Hengjumrut et al [46] where the bioavailability of asiaticoside was higher when administered as a single compound, than when it was administered as an extract to rats. Furthermore, the P app values for both the asiaticoside alone and the C. asiatica crude extract across the respiratory tissue were similar to the P app values previously reported for atenolol across respiratory (P app = 0.67 ± 0.11 × 10 −6 cm/s) and olfactory (P app = 2.78 ± 0.36 × 10 −6 cm/s) nasal epithelial tissues, a drug with poor to medium permeability [47].…”
Section: Ex Vivo Permeation Studies With Centella Asiatica Crude Extr...supporting
confidence: 85%
“…vivo study reported by Hengjumrut et al [46] where the bioavailability of asiaticoside was higher when administered as a single compound, than when it was administered as an extract to rats. Furthermore, the Papp values for both the asiaticoside alone and the C. asiatica crude extract across the respiratory tissue were similar to the Papp values previously reported for atenolol across respiratory (Papp = 0.67 ± 0.11 × 10 −6 cm/s) and olfactory (Papp = 2.78 ± 0.36 × 10 −6 cm/s) nasal epithelial tissues, a drug with poor to medium permeability [47]. In general, higher Papp values were obtained for the permeation of asiaticoside in the secretory direction than in the absorptive direction across the excised respiratory and olfactory tissue, which indicated it is subjected to active efflux transport.…”
Section: Ex Vivo Permeationsupporting
confidence: 85%